Parasitasi Trichogramma evanescens Westwood (Hymenoptera : Trichogrammatidae) pada Berbagai Tingkat Populasi dan Generasi Biakan Parasitoid terhadap Telur Penggerek Batang Jagung Ostrinia furnacalis Guenée - PABBAGE, M.S.; TANDIABANG, J. (AGRITROP; Vol. 26, No. 1 Maret 2007)
The parasitoid T. evanescens was reared in the laboratory, then; one, two, three, four, five, six female parasitoid respectively was released to one hundred eggs of ACB in the tube. The second experiment, the parasitoid was reared in the laboratory until ten, fifteen, twenty and twenty five generations, than released to one hundred eggs of ACB. The observation was done five days after releasing parasitoid. The result of the experiment showed that the maximum parasitism on the eggs of ACB 53.2% at four female parasitoid per hundred eggs of ACB. The increase of the number female parasitoid, the parasitism degree per one female parasitoid, and the emergence of the new parasitoid from egg were decreased. The parasitoid T. evanescens that reared in the laboratory by using substituted host Corcyra cephalonica was still effective up to tenth generations to control the eggs of ACB. Parasitoid that rearing after tenth generations, the parasitism degree, the new emergence parasitoid from the egg of ACB and walking or jumping speed of parasitoid was decrease.
Keywords: Parasitoid T. evenescens, eggs O. furnacalis, parasitism